DIGITALISASI PESANTREN DI ERA TRANFORMASI TEKNOLOGI DI YAYASAN ISLAM AL- GHAITSA DESA SUKARENDAH - Maulana, Akmal; Tazakka, Muhammad Adullah; Fitriana, Reva Helma; Millani, Aprilia; Ummah, Shopiyatul; Ikhsan, Maulana; Rahmayani, Ririn; Saputri, Salma Gusni; Ela, Ela; Wildan, M.; Hidayat, Syamsul (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Islamic boarding schools as traditional Islamic educational institutions in Indonesia have a very important role in developing human resources, especially in forming character and religious knowledge. Along with the rapid development of information and communication technology, digitalization of Islamic boarding schools has become a necessity to improve the quality of education, management efficiency and the relevance of Islamic boarding schools in modern society. This research aims to analyze the implementation of digitalization in Islamic boarding schools, the challenges faced, and the positive impacts that digital transformation can have in the Islamic boarding school education system. The method used in this research is literature study and interviews with several Islamic boarding school managers who have implemented technology in their operations. The research results show that the digitalization of Islamic boarding schools provides opportunities to increase access to information, introduce more flexible learning methods, and improve the quality of Islamic boarding school management. However, major challenges related to human resources which are still limited in mastering technology and the availability of adequate infrastructure must be overcome immediately to achieve optimal benefits.